Gambaran Sanitasi, Hygiene, Dan Keluhan Diare Pada Balita Usia 12-59 Bulan Di UPTD Puskesmas Rengas Kota Tangerang Selatan Tahun 2023 - Wibowo, Muhammad Azhar Ali; Wardani, Riastuti Kusuma (Journal of Religion and Public Health, 2024)
Diarrhea is the world's second leading cause of death for children under the age of five. The most common causes of diarrheal illnesses in toddlers are poor sanitation and hygiene. The purpose of this study is to describe sanitation, hygiene, and diarrhea concerns among toddlers working at Rengas Health Center in South Tangerang City. The variables examined were sanitation, hygiene, and diarrhea complaints. The design study was cross-sectional. The study included 82 kids aged 12-59 months by cluster random sampling. Univariate and bivariate were study analyzed. The study indicated that 37.8% of toddlers complained of diarrhea. Household waste management is known to fail to meet the requirements, with 42.4% of complaints of toddler diarrhea; CTPS fails to meet the requirements, with 60.6% of complaints of toddler diarrhea; and SPAL fails to meet the requirements, with 20% of toddler diarrhea complaints. Healthy Latrines and Stop Defecation had no respondents who did not satisfy the requirements, but there were reports of toddler diarrhea. The community in Rengas sub-district is required to collaborate with trash management institutions. Lastly, mothers and caregivers of toddlers should develop the habit of washing their hands with soap using appropriate and right steps at essential hand-washing times.Keywords: Diarrhea, Hygiene, Sanitation, Toddler